Evaluating The Integrated Environmental Management Of Municipal Solid Waste In Osaka City, Japan - Sintha Prima Widowati (Indonesian Journal of Geography, 2014)
Many state-of-the-art concepts and technologies on managing MSW have been developed for years. However, in Indonesia, the practice may still be insufficient because of the institutional capacity issue. This study aimed to evaluate the integrated environmental management for municipal solid waste in Osaka City, Japan. Method in use was descriptive analysis by literature review using official document “Environmental Management in Osaka City for Fiscal Year 1999” by Osaka City Environmental Bureau. Result showed Osaka City was adopting and modifying the Integrated Solid Waste Management (ISWM) suggested by Tchobanoglous et al. [1993] hierarchically using “Waste Reduction Principles” and establishing “Environmental Management Bureau” to handle the integrated solid waste management practice. More importantly, the implementation of ISWM was completely supported by the central government by law which was The Waste Disposal and Public Cleaning Law and by regulation which was the task distribution among central, prefectural and municipal government in managing the solid waste. These approaches were proven to be effectively implemented from top to bottom level thus should be recommended to the government of Indonesia.